1994
DOI: 10.1111/j.1365-2672.1994.tb03078.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and viability of coccoid forms of Campylobacter jejuni

Abstract: Studies were conducted into the formation and physiological state of coccoid cells of a strain of the human and animal pathogen Campylobacter jejuni. It was found that growth phase and the presence of chloramphenicol did not affect the rate of shape transformation from spiral to coccoid, while nutrient limitation, aeration of the medium and the presence of free-radical scavengers had profound effects. Coccoid cells were found to reduce the tetrazolium salts INT (2-(p-iodophenyl)-3-(p-nitrophenyl)-5-phenyl tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 15 publications
3
44
1
Order By: Relevance
“…Of note, a pH of 4.5 does not support the growth of C. jejuni NCTC 11168 (36 and our unpublished observations). Unfavorable growth conditions can lead to morphological changes in C. jejuni, causing a shift from a spiral to a coccoid shape (22,62,86,99). Microscopic analysis of the samples used for microarray analysis did not reveal the formation of coccoids or any other morphological variants under our experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Of note, a pH of 4.5 does not support the growth of C. jejuni NCTC 11168 (36 and our unpublished observations). Unfavorable growth conditions can lead to morphological changes in C. jejuni, causing a shift from a spiral to a coccoid shape (22,62,86,99). Microscopic analysis of the samples used for microarray analysis did not reveal the formation of coccoids or any other morphological variants under our experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…6A, panel 3). The coccoid cells are considered to be a degenerate bacterial form accumulated in cultures during prolonged incubation or are induced under unfavorable environmental conditions (6). We were interested to investigate if attached aggregates (biofilms) of bacteria provide a mechanism of protection from such conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Coccoid cells have other characteristics besides the obvious feature of their shape. It was revealed that, despite the presence of flagella, coccoid cells of C. jejuni are non-motile [17,21]. The lack of motility could be a repercussion of the morphology.…”
Section: Properties Of Coccoid Formsmentioning
confidence: 99%